THE ROLE OF TRADE AND ECONOMIC RELATIONS IN FORMING OF THE REGION DEVELOPMENT POTENTIAL: THEORETICAL AND APPLIED ASPECT - ZVARYCH, Ihor; DMYTRYSHYN, Lesia; ZVARYCH, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article investigates the impact of trade and economic relations on the development potential of the region formation in the context of regional theoretical concepts’ evolution. At the same time, with the use of systemic and synergistic approaches, methods of analysis and synthesis, induction and deduction, historical and comparative analysis, it was established that there are two approaches to economic growth and development in relation to the study of the development potential of the region: economic growth associated with an increase in gross product per capita, and its volumes. On the other hand, economic development is a broader concept and means an increase in the standard of living of a person, some of which have an immeasurable (qualitative) nature. At the same time, the list of regional development concepts given in the work gives an objective opportunity to assert that these are processes caused by differentiated factors. The influence of which accumulates during the period of determining the potential of the economic state of the region. However, it should be remembered that the factors considered in the theories of economic development are based mainly on the description of its regular processes that take place in the conditions of established, developed market economies. At the same time, the application of such factors from the point of view of modern changes taking place in the world economy, to clarify the trends of regional development in the countries of Eastern Europe, the economic processes of which are subject to the transformation of the economy in accordance with the requirements of European integration, definitely requires their expansion and adaptation.